Mediating Role of Career Development in the Relationship between Career Program and Personal Outcomes - Ismail, Azman; Madrah, Midaya; Ismail, Yusof (UI Scholars Hub, 2013)
This study was conducted primarily to measure the relationship between career program, career development and personal outcomes using self-administered questionnaires gathered from employees who have worked at a Sabah local government in Borneo. The outcomes of testing research hypothesis using a stepwise regression analysis showed two important findings: firstly, relationship between career program (i.e., planning and management) and career development positively and significantly correlated with job satisfaction. Secondly, relationship between career program (i.e., planning and management) and career development positively and significantly correlated with career commitment. Statistically, the result demonstrates that career development does act as an important mediating variable in the relationship between career program and personal outcomes in the career program model of the studied organization. The paper provides discussion, implications and conclusion.